Self-Regulated Online Learning and Students’ Attitude as Predictors of Skill Proficiency Development in Mathematics - Ken Clyde O. Longos; Rey M Regidor (USN Kolaka, 2022)
This study aimed to determine if self-regulated online learning and student’s attitude were predictors of skill proficiency development in Mathematics. 200 GE 4 students of UM North Campuses were the respondents of this research. The statistical tools used were Mean, Pearson-r, and Regression Analysis. Quantitative non-experimental research utilizing correlational technique with regression analysis was the research design of this paper. Results revealed high self-regulated online learning among GE 4 students in terms of metacognitive skill, time management, environmental structuring, persistence, and help seeking was high. The level of students’ attitude towards learning Mathematics yielded a descriptive equivalent of high confidence in Mathematics, the importance of Mathematics, and engagement in Mathematics. The level of skill proficiency development of the students in Mathematics yielded a high-level result in terms of conceptual understanding, procedural fluency, strategic competence, adaptive reasoning, and productive disposition. There was a positive significant relationship between self-regulated online learning and students’ attitude to skill proficiency development in Mathematics. However, between the two independent variables, students’ attitude was the only predictor of skill proficiency development in Mathematics.